The T allele of TCF7L2 rs7903146 is associated with decreased glucose tolerance after bed rest in healthy older adults - Fry, Jean L.; Munson, Brooke D.; Thompson, Katherine L.; Fry, Christopher S.; Paddon-Jones, Douglas; Arentson-Lantz, Emily J. (Scientific reports, 2022)
Inpatient populations are at increased risk of hyperglycemia due to factors such as medications, physical inactivity and underlying illness, which increases morbidity and mortality. Unfortunately, clinicians have limited tools available to prospectively identify those at greatest risk. We evaluated the ability of 10 common genetic variants associated with development of type 2 diabetes to predict impaired glucose metabolism. Our research model was a simulated inpatient hospital stay (7 day bed rest protocol, standardized diet, and physical inactivity) in a cohort of healthy older adults (n = 31, 65 ± 8 years) with baseline fasting blood glucose < 100 mg/dL. Participants completed a standard 75 g oral glucose tolerance test (OGTT) at baseline and post-bed rest. Bed rest increased 2-h OGTT blood glucose and insulin independent of genetic variant. In multiple regression modeling, the transcription factor 7-like 2 ( TCF7L2) rs7903146 T allele predicted increases in 2-h OGTT blood glucose (p = 0.039). We showed that the TCF7L2 rs7903146 T allele confers risk for loss of glucose tolerance in nondiabetic older adults following 7 days of bed rest.